Dermoscopic and trichoscopic features of primary cutaneous lymphomas – systematic review. (27th April 2021) - Sławińska, M.; Sokołowska‐Wojdyło, M.; Olszewska, B.; Nowicki, R.J.; Sobjanek, M.; Zalaudek, I.
Abstract: Dermoscopy and trichoscopy are non‐invasive methods used as auxiliary tools in diagnostics of different dermatoses. To date, no systematic review concerning the utility of dermoscopy and trichoscopy in the diagnostics of primary cutaneous lymphomas has been published. The aim of this study was to summarize the current state of knowledge on this topic based on systematic search of PubMed database and related references published before 8th of August 2020. Besides dermoscopic features, type of dermoscope, polarization mode, magnification, number of cases and histopathological correlation were analysed. A total of 34 records were included into the final analysis, evaluating 141 patients diagnosed with primary cutaneous T‐cell lymphomas and 70 patients with primary cutaneous B‐cell lymphomas. Most of the analysed records evaluated dermoscopic features (n = 206); trichoscopy was analysed in only 5 cases. Structures most commonly observed in classical mycosis fungoides (n = 108) were fine short linear vessels/linear vessels, spermatozoa‐like vessels and orange‐yellow patchy areas. In folliculotropic mycosis fungoides (n = 12), most frequently observed were comedonal lesions/comedo openings/central keratotic plugs and white halo around hair follicles/perifollicular accentuation. Primary cutaneous marginal zone B‐cell lymphoma (n = 42) and primary cutaneous follicle centre lymphoma (n = 20) most commonly presented with salmon‐coloured background and fine short/linear irregular/serpentine vessels. For other PCL, with less than 10 cases reported in the analysed records, details have been provided in the article. Most observations analysed in this systematic review rely on findings from case reports/case series (with the level of evidence V) and lack a control group. A few studies provided information concerning technical aspects of dermoscopic/trichoscopic examination. The role of dermoscopy/trichoscopy in diagnostics of cutaneous lymphomas requires further studies, especially in entities where dermoscopic features have been described in only single or a few cases. However, it seems that this practical, accessory tool in future may provide additional clues during clinical assessment.